Electrodeposition and structural characteristics of intermetallic nickel-tin based coatings. (2nd November 2017) - Georgiou, E. P.; Van der Donck, T.; Celis, J.-P.
Abstract : Ni–Sn alloy intermetallic coatings with different Sn contents, were electrodeposited on Vanadis 23 steel substrates. Structural and chemical characterisation of these coatings was performed by x-ray diffraction, scanning electron microscopy and electron dispersive x-ray analysis. The as-plated Ni–Sn coatings were found to consist of a crystalline Ni solid solution with dispersed Ni–Sn intermetallic phases, whereas in certain cases bulk intermetallic coatings were obtained. The addition of Sn as an alloying element into electrolytic Ni coatings led to a significant increase of hardness and Young's modulus of these coatings. In addition, the effect of a post-deposition heat treatment at 400°C for 1 h on the microstructure and mechanical characteristics of these electrolytic Ni–Sn alloy coatings was investigated.